2017
DOI: 10.1016/j.ijcard.2017.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx shedding is markedly increased during the acute phase of Takotsubo cardiomyopathy

Abstract: TTC is associated acutely with a marked increase in GCS. Potentially, GCS might contribute to increased coronary vascular permeability in TTC, thus dissociating development of myocardial oedema from severity of associated inflammation. Prevention of GCS represents a potential therapeutic option in TTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…In support of this possibility, syndecan-1 levels noted in the Brazilian cohort of patients with acutely decompensated heart failure [16] were much higher than in the currently evaluated patients. In our centre, we have also observed that in patients with acute takotsubo cardiomyopathy, plasma syndecan -1 levels were much higher (97 ± 65ng/ml) [31] than in our cohort of patients with chronic HFrEF, who were already receiving optimal medical treatment.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In support of this possibility, syndecan-1 levels noted in the Brazilian cohort of patients with acutely decompensated heart failure [16] were much higher than in the currently evaluated patients. In our centre, we have also observed that in patients with acute takotsubo cardiomyopathy, plasma syndecan -1 levels were much higher (97 ± 65ng/ml) [31] than in our cohort of patients with chronic HFrEF, who were already receiving optimal medical treatment.…”
Section: Discussionsupporting
confidence: 50%
“…There was also no significant correlation between changes in LVEF post-CRT and those in syndecan-1 levels at 6 months, (r=0. 31…”
Section: Effects Of Crtmentioning
confidence: 99%
“…We showed, in female rats injected with isoproterenol, that precipitation of TS-like echocardiographic changes (29) was associated with intramyocardial accumulation of 3-NT, a conventional marker of nitrosative stress (19) , and of PAR, a product of PARP-1 activation and thus a marker and mediator of myocardial energetic impairment (30) . Myocardial TXNIP content was also significantly increased after ISO administration, consistent with increased stimuli for its expression, such as withdrawal of NO effect (25) and/or disruption of laminar flow and associated shear stress (31) ; this process known to be precipitated by glycocalyx shedding, a recently delineated component of TS (32) . We also reported the presence of inflammatory infiltrate, with a substantial increase in CD68+ cells, representing predominantly macrophage/monocyte infiltration.…”
Section: Discussionmentioning
confidence: 62%
“…Third, myocardial energetic impairment persists for at least 4 months after acute attacks of TS (10) . Finally, glycocalyx shedding occurs in the acute stages of TS (32) , which increases cellular permeability and may contribute to the prolonged and characteristic accentuation of myocardial edema (33) in this condition. A schematic representation of these findings is provided in Figure 9 .…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of acute and chronic cardiac disorders which are characterised by the presence of myocardial infiltration by neutrophils, with associated tissue inflammation, and with both the marked release of BNP and the activation of glycocalyx shedding—a result of the impact of a range of matrix metalloproteinases [5]. These include, in particular, acute myocardial infarction [51] and takotsubo syndrome [52], a catecholamine-initiated form of acute myocardial inflammation. In both of these conditions, myocardial infiltration by neutrophils and monocyte/macrophages is prominent.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%